Computer aided apparel pattern-making application - Koh, Thong Hwee. (2009)
In apparel mass manufacturing, garments are produced through several processes involving a variety of skills. Fashion designs are first defined and illustrated through sketches. These fashion sketches are transformed into flat pattern pieces, which are subsequently graded over a range of sizes. The graded pattern pieces are then nested on rectangular markers, like jigsaw puzzles, to ensure efficient utilization of material. These markers are used to cut the fabric for the pattern pieces to be sewn into finished garments.